El espectro radioeléctrico: recurso esencial para los servicios de comunicaciones móviles que demanda óptima utilización - Rodríguez Jiménez, Carlos Eduardo; Betancourt Uscátegui, Álvaro (Ingeniería, 2000)
The intensive use of services that require for their operation of the radioelectric spectrum is demanding a much better availability of this natural resource.Due to it´s depletability it becames necessary the maximization of this spectrum´s use, mainly by the means of the development of an effective management. Essential supports to carry out this task, are the knowledge about the current use of this resource, the dynamic flow of information among the actors of the sector, and having the necessary resources that allows to carry out the different computing tasks, programming and execution of the specific technical confirmation processes, the data adaptation and the analysis and presentation of the information. This paper presents, arguments in favor of the revision of these factors showing briefly the international interest and the current state in the internal environment, as well as the development of a database that facilitates the use and spectrum management.